Succession and Transformation of the American Strategy to the Middle East - Hadziev, Boyan (Research Papers, 2020)
The Middle East is one of the most turbulent regions in the world, and its resource potential makes it a major field for geopolitical clashes. The American strategy in this region is in many cases contradictory, almost always pragmatic, but often based on idealistic motives. The context analysis, the policies and the means the United States implement allows the essence of the American strategy to be traced and evaluated – whether it is transforming and how.
Keywords: Middle East; U.S.; Presidential doctrines; Strategy